Amyloid β-induced Mesenteric Inflammation in an Alzheimer’s Disease Transgenic Mouse Model - Ano, Yasuhisa; Ikado, Kumiko; Uchida, Kazuyuki; Nakayama, Hiroyuki (Current Alzheimer Research, 2020)
Background: Alzheimer’s disease (AD) is a neurodegenerative disorder histopathologically characterized by the accumulation of amyloid β (Aβ) peptides and inflammation associated with activated microglia. These features are well investigated in the central nervous system using AD-model mice; however, peripheral inflammation in these mice has not been investigated well. Objective: We evaluated the inflammatory responses, especially myeloid dendritic cells (mDCs), in peripheral lymphoid tissues in AD-model mice to determine their association with Aβ deposition. Methods: We collected lymphocytes from mesenteric lymphoid nodes (MLNs) and Peyer’s patches (PPs) of 5xFAD transgenic mice used as an AD model. Lymphocytes were analyzed using a flow cytometer to characterize mDCs and T cells. Collected lymphocytes were treated with Aβ1-42 ex vivo to evaluate the inflammatory response. Results: We observed elevated levels of inflammatory cytokines and chemokines including interleukin (IL)-12 and macrophage inflammatory protein-1α in mDCs from MLNs and PPs and reduced levels of programmed death-ligand-1, an immunosuppressive co-stimulatory molecule, on the surface of mDCs from 5xFAD mice. Additionally, we found increases in interferon (IFN)-γ-producing CD4- or CD8- positive T cells in MLNs were increased in 5xFAD mice. Moreover, ex vivo treatment with Aβ peptides increased the production of IL-12 and IFN-γ by lymphocytes from 5×FAD mice. Conclusion: The present study showed that pro-inflammatory mDC and T cells were induced in MLNs and PPs of 5xFAD mice.
Keywords: myeloid dendritic cells